Current laboratory practices in the diagnosis and management of haemophilia: a global assessment. (16th February 2015) - Kitchen, S.; Signer‐Romero, K.; Key, N. S.
Summary Haemophilia management is complicated by the extreme variability in laboratory practices. Lack of consistency or comparability in testing makes it difficult to establish diagnostic criteria or disease severity, and complicates response assessment. A global survey was conducted to document current practices. A 35‐min survey was completed by 30 laboratory scientists in each of seven countries (France, Germany, Italy, Japan, Spain, UK, USA; 210 in total); results were weighted by average country testing volume in haemophilia. Eighty‐three per cent of participants reported participation in a Quality Assurance scheme. Ninety per cent reported using clotting tests in haemophilia A and 88% in haemophilia B (55% and 53% frequent use respectively). Sixty‐eight per cent reported chromogenic assays were used in haemophilia A, with only 23% reporting frequent use, compared to only 11% reporting any use in haemophilia B. Twenty‐nine separate activated partial thromboplastin time (aPTT) reagents were reported for haemophilia A and 27 aPTT reagents were reported for haemophilia B, with one‐quarter or less obtaining reagents or kits from any single manufacturer. Fifty‐four per cent run a calibration curve with every factor VIII (FVIII) assay. The mean number of plasma dilutions varied from 2 to 4 for FVIII assays and from 1 to 3 for FIX assays. Results indicate very low consistency in materials and practices used to test for factor activity in haemophilia. A number of responses suggest that some laboratory scientists' understanding of best practices or guidelines in haemophilia could be improved. More education and broader understanding is recommended regarding assay types, assay components, test material and instrument features and capabilities.